THE EFFECT OF JOB DESCRIPTION AND WORK COMMUNICATION ON MEDICAL MEDICAL EMPLOYEE PERFORMANCE AT PT. PAMELA MEDIKA NUSANTARA TEBING TINNGI - Alexander; Andres Rodriguez-Clare (PT. Radja Intercontinental Publishing, 2023)
This study uses Primary Data, namely data sources that directly provide data to data collectors. In this study, the primary data was in the form of data from questionnaires and interviews conducted by researchers. In this study, the population was 120 customers of PT. Sri Pamela Medika Nusantara Tebing Tinggi, Tebing Tinggi City, in the last 3 months. From the basis for determining the writer's sample based on the Slovin formula with an error tolerance of 10%, the number for the sample is 55 respondents. The results of the first study are accepted, meaning that the Job Description Variable (X1) has a significant effect on Medical Employee Performance Variable (Y). the second hypothesis is accepted, meaning that the Work Communication Variable (X2) has a significant effect on the Medical Employee Performance Variable (Y). the third hypothesis is accepted, meaning that the Job Description Variable (X1), Work Communication Variable (X2) have a significant simultaneous effect on Medical Employee Performance Variable (Y).